The appointment of members of the Supreme Court of the United States of America : reflecting on the appointment of of the Supreme Court (Revista do Tribunal Regional Federal da 3ª Região, 2019)
Considering the importance of the Supreme Courts in the western societies, it will be analized the proceedings for the nomination of the Supreme Court ministers in the USA, in order to provide – for Brazilian jurists – a comparative and reflexive tool about the nomination process regarding the STF ministers in Brazil.
Keywords: nomination; Supreme Court; USA; Federal Court of Justice; Judicial power; balance between the three powers